Prevalence and profile of Neurodevelopment and Fetal Alcohol Spectrum Disorder (FASD) amongst Australian Aboriginal children living in remote communities. (June 2017) - Fitzpatrick, James P.; Latimer, Jane; Olson, Heather Carmichael; Carter, Maureen; Oscar, June; Lucas, Barbara R.; Doney, Robyn; Salter, Claire; Try, Julianne; Hawkes, Genevieve; Fitzpatrick, Emily; Hand, Marmingee; et al.
Highlights: Neurodevelopmental assessment of Australian Aboriginal children (7–9 years old). One third of this population identified as having a neurodevelopmental disorder. Very high prevalence conditions on the FASD spectrum were identified (194.4/1000). Impairment found in multiple CNS domains associated with prenatal alcohol exposure. Abstract: Background: Despite multiple risk factors for neurodevelopmental vulnerability, few studies have assessed neurodevelopmental performance of Australian Aboriginal children. An important risk factor for neurodevelopmental vulnerability is prenatal alcohol exposure (PAE), which places children at risk for Fetal Alcohol Spectrum Disorder (FASD). Aims: This study assesses neurodevelopment outcomes in a population of Australian Aboriginal children with and without PAE. Methods and procedures: Children born in 2002/2003, and living in the Fitzroy Valley, Western Australia between April 2010 and November 2011, were eligible ( N = 134). Sociodemographic and antenatal data, including PAE, were collected by interview with 127/134 (95%) consenting parents/caregivers. Maternal/child medical records were reviewed. Neurodevelopment was assessed by clinicians blinded to PAE in 108/134 (81%) children and diagnoses on the FASD spectrum were assigned. Outcomes and results: Neurodevelopmental disorder was documented in 34/108 children (314.8 per 1000). Any diagnosis on the FASD spectrum was made in 21/108 (194.4 per 1000) children (95% CI = 131.0–279.0). Conclusions and implications: Neurodevelopmental impairment with or without PAE is highly prevalent among children in the Fitzroy Valley. Rates of diagnoses on the FASD spectrum are among the highest worldwide. Early intervention services are needed to support developmentally vulnerable children in remote communities.